Towards entrepreneurial universities: barriers, facilitators, and best practices in Bulgarian and Portuguese universities - Yordanova, D. (2020)
Purpose: Тhe main objective of this research is to investigate barriers, facilitators and best practices in the transformation of Bulgarian and Portuguese universities into entrepreneurial universities. Design/Methodology/Approach: This study relies on a survey among experts in the field to identify barriers, facilitators and best practices in the transformation of Bulgarian and Portuguese universities into entrepreneurial universities. Findings: The research findings demonstrate that there are both internal and external barriers and facilitators of the entrepreneurial transformation of universities in Bulgaria and Portugal and reveals the relative importance of the various internal and external factors. The study describes several best practices in the transformation towards an entrepreneurial university adopted at Sofia University “St. Kliment Ohridski” and ISCTE-IUL. Practical Implications: This research raises awareness of the internal challenges to making Bulgarian and Portuguese universities more entrepreneurial as well as of factors that may facilitate the process of transformation and the need to strengthen entrepreneurship ecosystem at these universities. Policy makers should devote special attention to external barriers to the transformation and especially to the need for more appropriate legal framework and more state funding. Originality/Value: The study highlights that the relative importance of the various internal and external factors is context specific.